Company valuation – modern day dilemmas - Elżbieta Rak-Młynarska; Aleksandra Skobelska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Valuation of a company is a very complex and challenging task. On one hand it requires the orientation in the existing analytical tools and relies on selection of appropriate valuation methods, and on the other it is quite intuitive with respect to the choice of unquantifiable factors. Re-occurring crisis situations which are triggered by decisions taken upon partial or manipulated information call for a critical review of popular valuation methods and development of new more optimal solutions for company valuation.